Criteria to Evaluate the Commercialization of Scientific and Technological Research from Economic Universities - Pham Duong Phuong , Thao; Huynh , Duc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
Commercialization and transfer of scientific research results is one of the important activities that are concerned by countries. Currently, in Vietnam, many universities have been actively implementing research activities, implementing technology transfer and commercializing research results. However, these activities are mostly concentrated in the technical sector with the characteristics of applied research to create new tangible products or services; In the economic sector, due to its own characteristics, commercialization is difficult to carry out. With the desire to contribute to the development of Vietnam's science and technology market, the authors conducted a case study at three key universities, including: National Economics University, University of Economics Ho Chi Minh City, Ho Chi Minh City Open University. On that basis, the authors develop a set of criteria to evaluate the commercialization of scientific and technological products from universities in the economic sector with 26 specific criteria and propose a few development solutions based on the studies here.
Keywords: Criteria set of evaluating; Economics sector; Commercialization; Transfer of results; Scientific research